2015
DOI: 10.3390/nu7042237
|View full text |Cite
|
Sign up to set email alerts
|

The Infant Gut Microbiome: Evidence for Obesity Risk and Dietary Intervention

Abstract: Increasing globally, particularly in children, obesity is a serious public health issue and risk factor for overweight and metabolic disease in later life. Both in experimental animal and human studies, advances in gene sequencing technologies have yielded intriguing possibilities for the role of the gut microbiome in later development of overweight status. Before translating study findings into practice, we must first reconcile inconsistencies between animal experimentation, and human adult and infant studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 107 publications
1
107
0
3
Order By: Relevance
“…Therefore, research into factors affecting the gut microbiota has become an area of growing scientific interest. The gut microbiota is influenced by various factors, including the microbial species acquired at birth, age, host genotype, geography, and diet [6][7][8][9]. Of these, diet is considered a key contributor to the diversity of the gut microbiota, explaining 57% of the total structural variation, while only 12% is related to genetic differences [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research into factors affecting the gut microbiota has become an area of growing scientific interest. The gut microbiota is influenced by various factors, including the microbial species acquired at birth, age, host genotype, geography, and diet [6][7][8][9]. Of these, diet is considered a key contributor to the diversity of the gut microbiota, explaining 57% of the total structural variation, while only 12% is related to genetic differences [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, prebiotics have been used to prevent or treat obesity. Compared to probiotics, human studies with prebiotics have shown more promising results in obesity management, with reductions in body weight and fat mass in adults [82][83][84] in contrast with results from meta-analysis mentioned above, where the supplementation with prebiotics was signiicantly associated to a higher weight gain [80].…”
Section: Type Of Infant Feedingmentioning
confidence: 98%
“…Several randomized controlled trials have been made to evaluate the eicacy and safety of prebiotic supplementation in infant formulas [78,79]. After compiling data of these trials into a meta-analysis, weight gain [weighted mean diference 1.07 g/day] was signiicantly higher among formula-fed infants supplemented with prebiotics compared to the placebo group [80]. In addition, a large number of clinical trials in term of infants have shown controversial results related to the increase in Biidobacteria in feces due to supplementation of infant formula with GOS and FOS.…”
Section: Type Of Infant Feedingmentioning
confidence: 99%
“…Variations in the antioxidant status in parts of the human colon are due exclusively to the fermentation processes of microorganisms in microbiota in the digestive tract [Koleva et al, 2015]. The total antioxidant activity of the formulation based on lyophilized mycelia of P. ostreatus and L. edodes is shown in Figure 1 (FRAP method) and Figure 2 (ABTS method).…”
Section: Antioxidant Effects Of Mushroom Myceliamentioning
confidence: 99%